Tribology of natural Poly-Ether-Ether-Ketone (PEEK) under transmission oil lubrication - Andrade,Thiago Fontoura de (2019)
Abstract High performance polymeric materials such as poly-ether-ether-ketone (PEEK) are increasingly being used for challenging tribological applications in order to replace metal parts in vehicle engines and transmissions. The tribology of natural PEEK, under oil-lubricated conditions, was studied for different metal counterbody finishes. Two different finishing processes were selected for this study: turning and polishing. The test system used was a tri-pin on disc, with pins made of PEEK and counterbodies made of steel, and then dipped in ATF Dexron VI oil. The conclusion was that the wear rate generated by turning was about seven times as high as the wear rate generated by polishing. The friction coefficient displayed a direct correlation with the lubrication regime, and the level of counterbody roughness. On average, the friction coefficient on the hydrodynamic regime for polishing was more than 3 times lower than the friction coefficient in the boundary regime for turning.